THE EFFECT OF RISK TOLERANCE ON CRYPTOCURRENCY INVESTMENT DECISIONS - Nur Aini; AHMAD RIFA'I (Indragiri Research Center (ingreat), 2023)
This research was conducted with the aim of knowing whether there is an effect of risk tolerance on cryptocurrency investment decisions. In this study, data analysis used a simple regression analysis method using the SPSS Statistics 25 application. Data sources used primary and secondary data while data types used quantitative data with an associative approach. The research population that was conducted by the researchers were active and inactive investors in cryptocurrency investing with a sample of 96 people from a small number of sub-districts across Indonesia. With data collection techniques through a questionnaire using a Likert scale. Based on the results of the t test, there is a significant influence of the Risk Tolerance variable on Cryptocurrency Investment Decisions